Feasibility of an Autism-Focused Augmented Reality Smartglasses System for Social Communication and Behavioral Coaching - Liu, Runpeng; Salisbury, Joseph P.; Vahabzadeh, Arshya; Sahin, Ned T. (Frontiers in Pediatrics, 2017)
Background: Autism Spectrum Disorder (ASD) is a childhood-onset neurodevelopmental disorder with a rapidly rising prevalence, currently affecting 1 in 68 children, and over 3.5 million people in the United States. Current ASD interventions are primarily based on in-person behavioral therapies that are both costly and difficult to access. These interventions aim to address some of the fundamental deficits that clinically characterize ASD, including deficits in social communication, and the presence of stereotypies, and other autism-related behaviors. Current diagnostic and therapeutic approaches seldom rely on quantitative data measures of symptomatology, severity, or condition trajectory. Methods: Given the current situation, we report on the Brain Power System (BPS), a digital behavioral aid with quantitative data gathering and reporting features. The BPS includes customized smartglasses, providing targeted personalized coaching experiences through a family of gamified augmented-reality applications utilizing artificial intelligence. These applications provide children and adults with coaching for emotion recognition, face directed gaze, eye contact, and behavioral self-regulation. This preliminary case report, part of a larger set of upcoming research reports, explores the feasibility of the BPS to provide coaching in two boys with clinically diagnosed ASD, aged 8 and 9 years. Results: The coaching intervention was found to be well tolerated and rated as being both engaging and fun. Both males could easily use the system, and no technical problems were noted. During the intervention, caregivers reported improved non-verbal communication, eye contact, and social engagement during the intervention. Both boys demonstrated decreased symptoms of ASD, as measured by the Aberrant Behavior Checklist at 24 hours’ post-intervention. Specifically, both cases demonstrated improvements in irritability, lethargy, stereotypy, hyperactivity/noncompliance, and inappropriate speech. Conclusions: Smartglasses using augmented reality may have an important future role in helping address the therapeutic needs of children with ASD. Quantitative data-gathering from such sensor-rich systems may allow for digital phenotyping and the refinement of social communication constructs of the Research Domain Criteria (RDoC). This report provides evidence for the feasibility, usability, and tolerability of one such specialized smartglasses system.